Gifts reserved for age: a Lacanian study of comedy in Philip Roth’s Exit Ghost - DOI: 10.4025/actascilangcult.v32i1.4681 - Mellard, James Milton (Acta Scientiarum. Language and Culture, 2009)
The critical problem surrounding Philip Roth’s recent Exit Ghost (2007), the ninth and projected by the author as the final Zuckerman novel, is how it can function as comedy when one major character is dying of brain cancer and its protagonist is seventy-one years old, beginning to receive an elderly male’s gifts reserved for age –prostate cancer, prostate surgery, impotence, and incontinence – and, despite all, falls in love with a thirty-year-old married woman. A sequel to The Ghost Writer (1979), the first Zuckerman novel, whose character relations it repeats, Exit Ghost has comparatively less humor than its predecessor but there is humor enough. Moreover, and more important, it fits the genre of comedy because of the functions it gives to the classically traditional motifs of the phallus, castration, age versus youth, Eros and Thanatos, and the like. It is from a Lacanian critical perspective that it can be shown how the novel moves toward comedy’s conventional happy ending because of the duality of meanings attached to the matter of castration, the way in which Roth/Zuckerman displaces the object of desire from the young woman and finds it – enjoyment, jouissance – in the very process of writing itself.